2019
DOI: 10.1007/s12098-019-02960-1
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Injury with Continuous Positive Airway Pressure: Need for “Privileging” Nursing Staff

Abstract: Objectives Use of continuous positive airway pressure (CPAP) in neonates is associated with nasal injury (NI) for which various risk factors related to the neonatal characteristics and properties of interfaces used have been reported. BPrivileging^of nursing staff may influence safety and incidence of adverse events. In this prospective cohort study, authors studied the incidence of NI and risk factors for NI in babies requiring CPAP after privileging staff for CPAP care bundles. Methods All neonates on CPAP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…The maintenance of noninvasive respiratory support equipment and appropriate cleaning has to be done on a regular basis. The training of nurses for managing neonates on noninvasive support decreases the incidence of nasal trauma [ 37 ]. Quality improvement measures like using a nCPAP cart, prepacked fixation kits, a written nursing protocol, ensuring adherence to manufacturers recommendations and evidence-based checklists are effective measures to expedite nCPAP initiation and decrease nasal trauma [ 38 , 39 ].…”
Section: Supportive Carementioning
confidence: 99%
“…The maintenance of noninvasive respiratory support equipment and appropriate cleaning has to be done on a regular basis. The training of nurses for managing neonates on noninvasive support decreases the incidence of nasal trauma [ 37 ]. Quality improvement measures like using a nCPAP cart, prepacked fixation kits, a written nursing protocol, ensuring adherence to manufacturers recommendations and evidence-based checklists are effective measures to expedite nCPAP initiation and decrease nasal trauma [ 38 , 39 ].…”
Section: Supportive Carementioning
confidence: 99%
“…18,22 However, several studies have evaluated changes in the frequency of nasal injuries after nurses receive NIV-related nasal injury prevention training. 8,12,21 Naha et al 8 reported that the frequency of nasal injuries was 11% among infants in the care of nurses who received training and 66% among those cared for by nurses who did not receive training. Mariam and Buddhavarapu 21 developed a nasal continuous positive-airway pressure (nCPAP) checklist and a quality improvement initiative related to the implementation of the checklist.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers developed this form based on the literature to evaluate nurses' level of knowledge about evidence-based interventions to protect preterm infants from nasal MDRPI. 8,21,[28][29][30] The form consists of 40 questions in five sections: neonatal skin structure, medical device injury, skin assessment tools, NIV injury, and NIV injury prevention interventions. The nurses were asked to agree or disagree with the statement given in each item.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 2 more Smart Citations